NMR Methods for Quantitative Isotopomer Rates in Real-Time Metabolism of Cells - Michelle Ac Reed; Roberts, Jennie; Gierth, Peter; Kupce, Eriks; Guenther, Ulrich L (bioRxiv, 2019)
Tracer-based metabolism is becoming increasingly important to study metabolic mechanisms in cells. NMR offers several approaches to measure label incorporation in metabolites, including 13C and 1H-detected spectra. The latter are generally more sensitive but quantification depends on the proton carbon 1JCH coupling constant which varies significantly between different metabolites. It is therefore not possible to have one experiment optimised for all metabolites and quantification of 1H-edited spectra such as HSQCs requires precise knowledge of coupling constants. Increasing interest in tracer-based and metabolic flux analysis requires robust analyses with reasonably small acquisition times. Here we compare 13C-filtered and 13C-edited methods for quantification with a special focus towards application in real-time NMR of cancer cells under near-physiological conditions. We find an approach using a double-filter most suitable and sufficiently robust to reliably obtain 13C-incorporations from difference spectra. This is demonstrated for JJN3 multiple myeloma cells processing glucose over 24h.